An analysis of Students' Perception on Paper and Electronic Dictionary in Writing Skills at the Ninth Grade of SMP Negeri 1 Takalar - Awaliyah, Riska; Abdul, Nurdevi Bte; Daddi, Herlina (FKIP Unismuh Makassar, 2020)
This research has been designed to analyze students’ perception on paper and electronic dictionary to the students who studied at SMP Negeri 1 Takalar. This research used descriptive qualitative method. To obtain data of this research, the researcher used interview as an instrument. This research used 14 questions as the instrument for data collection. There were 22 students involved as participants of this research, they were selected by using purposive sampling technique.The result of this research revealed that students’ perception on paper and electronic dictionary. There were five of students’ perception toward paper dictionary such as paper dictionary was easy to use for students, paper dictionary helps students in writing skills, paper dictionary is easy to be carried, paper dictionary less costly than buying electronic dictionary and paper dictionary enhances students learning. On the other side, there were six of students’ perception toward electronic dictionary such as electronic dictionary was easy to use for students, electronic dictionary helps in writing skills, electronic dictionary is easy to be carried, many features are used in electronic dictionary, electronic dictionary less costly than buying paper dictionary, and electronic dictionary enhance students' learning. Therefore, it can be concluded that paper and electronic dictionary can help students in writing skills, but paper dictionary is more effectively can enhance students’ learning. Electronic dictionary is mostly used by the students. Paper dictionary has become a tool that easy to use for students and electronic dictionary has become a tool for the probability in which easy to be carried for students. The use of paper and electronic dictionary gives impacts for language learning.